DISTINGUISHING THE FORMS OF COMMON PURPOSE LIABILITY S v Govender 2023 (2) SACR 137 (SCA) - Shannon Hoctor (Obiter, 2024)
In the case of S v Govender (2023 (2) SACR 137 (SCA)), the Supreme Court of Appeal (SCA) was required once again to examine the common purpose doctrine, which although it has been in use in South African law for the past century, has in recent years seen significant development, in its expansion from being applied solely to a prior agreement, to also being applied in the case of an active association between two or more persons. The importance of distinguishing between these different forms of the common purpose doctrine has concomitantly also become increasingly important.As the court points out in S v Mzwempi (2011 (2) SACR 237 (ECM) par 56), prior-agreement common purpose encompasses “any conduct which falls within the wide and general common design”, whereas active-association common purpose is “restricted to particular conduct”. Thus, in active-association common purpose, the association is with a “specific act” by which the crime was committed by another participant in the common purpose. It follows that, given the “marked differences” between the two forms of common purpose:“in a case where the state seeks to place reliance on the doctrine of common purpose, the trier of fact will be required to determine the nature of the common purpose relied upon, what the scope of that common purpose happened to be, and whether the accused was a participant, and remained a participant, in the common purpose.”The discussion examines the significance of the distinction between the different forms of common purpose doctrine, in light of the SCA judgment in the case of Govender.